Principles' Training Programs and Transformational Leadership and Its Effect on School Quality Management Implementation - Ridho Frihastama; Hermanto Hermanto (STAI Hubbulwathan Duri, 2022)
The aim of this study is determining the effect of the principal's transformational leadership, the commitment of educators and education personnel, and training programs on the implementation of school quality management and performance. This research is considered as quantitative research. The population in the study is all Malang teachers. 100 Malang teachers are used as samples selected by simple random sampling. The data in this study is obtained by distributing questionnaires through G-Form distributed to each school's group. The collected data is analyzed using Structural Equation Model (SEM). The results of the test show that Transformational Leadership has an effect on the Implementation of Quality Management. Transformational Leadership affects Institutional Performance, Commitment of Educators and Education Personnel affects Quality Management Implementation, Educator and Educational Personnel Commitment affects Institutional Performance, Training Programs affect quality management, training programs affect Institutional Performance. This research is hoped to contribute to the educational literature and have beneficial throughout larger society, especially in educational field.